HR-ENHANCING PRACTICES: A METHODOLOGY REVIEW - Asmaa abdulwaheid malik alghnimi; Yas Khudhair Abbas; Israa Abdulhasan Oleiwi (Journal Park Publishing, 2024)
The current study aims to comprehensively present a set of studies that dealt with the subject of enhanced practices of human resources to highlight the importance of these practices between academic and administrative thought in particular; the object of improved human resource practices focuses on the implementation of strategies and policies targeted at improving human resource performance in institutions. These strategies attract and retain top people, develop employees' skills and capacities, increase employee satisfaction, and ensure job security. Thus, these approaches strive to improve human resource performance and make the most of employees' capabilities and skills. Overall, it contributes to creating a happy and healthy work environment, as well as increased employee satisfaction and commitment, ultimately leading to achieving company objectives and long-term success.